Numerical simulation of couple stress nanofluid flow in magneto-porous medium with thermal radiation and a chemical reaction - Sithole, Hloniphile; Mondal, Hiranmoy; Goqo, Sicelo; Sibanda, Precious; Motsa, Sandile (Applied mathematics and computation, 2018)
We present a study of heat and mass transfer for a couple stress nanofluid flow in a magneto-porous medium with thermal radiation and heat generation. The flow is generated by a stretching surface and the temperature and concentration distributions are studied subject to nanoparticle Brownian motion and thermophoresis effects. The nonlinear model equations have been solved using a spectral quasi-linearization method. The solution method has been used in a limited number of studies in the resent past. Its general reliability for a wider range of problems remains to be determined. Thus in order to determine the accuracy of the solutions, and the convergence of the method, a qualitative presentation of residual errors for different parameters is given. Additionally, for some special flow cases, the current results have been compared with previously published work and found to be in good agreement. A limited parametric study showing the influence of the flow parameters on the fluid properties is given. The numerical analysis of the residual error of PDEs and convergence properties of the method are also discussed. The method is computationally fast and gives very accurate results after only a few iterations using very few grid points in the numerical discretization process. The aim of this manuscript is to pay more attention of residual error analysis with heat and fluid flow on couple stress nanofluids to improve the system performance. Also the fluid temperature in the boundary layer region rise significantly for increasing the values of thermophoresis and Brownian motion parameter. The results show that wall shear stress increases by increasing couple stress parameter.